Dinamika Komunikasi dalam penguatan perempuan komunitas pembatik desa gumeng mojokokerto - Fatihatul Lailiyah (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
Women’s empowerment is a crucial strategy for promoting inclusive and sustainable rural development. This study aims to examine the dynamics of communication in the process of socio-economic empowerment of women in the batik community in Gumeng Village, Mojokerto Regency. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participant observation, and documentation involving women members of the batik community and relevant stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing.The findings indicate that the batik community plays a significant role in enhancing women’s economic independence by strengthening batik-making skills and contributing to household income. Socially, the community serves as a space for strengthening social capital, increasing self-confidence, and expanding women’s roles within the family and society. However, the empowerment process remains constrained by limited access to capital, market reach, and institutional support. This study concludes that the batik community functions not only as an economic production unit but also as a medium for social transformation and women’s empowerment based on local creative economy.